Endovascular management of acute and subacute venous thoracic outlet syndrome - Davies, Mark G.; Hart, Joseph P. (Frontiers in Surgery, 2024)
Approximately 3% of all patients presenting with Thoracic Outlet Syndrome have a venous etiology (vTOS), which is considered "effort thrombosis". These patients will present with symptomatic deep venous thrombosis or focal subclavian vein (SCV) stenosis. Endovascular management of vTOS occurs in several phases: diagnostic, preoperative therapeutic intervention before decompression, postoperative interventions after decompression, and delayed interventions in the follow-up after decompression. In the diagnostic phase, dynamic SCV venography can establish functional vTOS. Approximately 4000 patients have been treated for vTOS and reported in the literature since 1970. Declotting of the SCV was followed by surgical decompression in 53% of patients, while in the remainder, surgical decompression alone (18%), endovascular intervention alone (15%), or conservative therapy with anticoagulation (15%) was performed. The initial intervention was predominantly catheterdirected thrombolysis, with <10% of cases undergoing concomitant balloon angioplasty. 93% of cases were successful. In the postoperative phase, balloon angioplasty was performed to correct residual intrinsic SCV disease after vTOS decompression in under 15% of cases.Stents were rarely deployed. Symptom relief was reported as 94±12% (mean ± SD) and 90±23%, respectively for declotting with decompression and declotting alone. In the delayed phase, balloon angioplasty was performed in under 15% of cases to re-establish patency.